Maize Lethal Necrosis (MLN) – Prevention and management - Mahabaleswara, Suresh L. (International Maize and Wheat Improvement Center, 2022)
The Maize Lethal Necrosis (MLN) disease of maize emerged in eastern Africa in 2011-2012, affecting the food security and livelihoods of several million smallholder farmers. Intensive efforts by CGIAR, together with national and international partners, helped in implementing a modern surveillance and monitoring system, spread improved agricultural practices for the disease control, deploy MLN-tolerant/resistant varieties, and curb the spread of the disease through safe germplasm exchange and distribution. An MLN Phytosanitary Community of Practice was established among national plant protection organizations and commercial seed sector. MLN is still prevalent however in eastern Africa. Continued efforts are needed through the CGIAR Plant Health Initiative to implement MLN monitoring and management strategies to contain the disease in eastern Africa, and prevent its spread to other regions in sub-Saharan Africa.